Kepemimpinan Kepala Sekolah dan Kompetensi Guru Dalam Meningkatkan Prestasi Belajar Siswa - Solihah, Siti (Universitas Koperasi Indonesia, 2023)
This study aims to know and analyze the influence of Principal Leadership and Teacher Competence on Student Learning Achievement (Case Study on MA Ibnu Rusyd and MA Al- Jawami Bandung Regency). The population in this study was 41 teachers of MA Ibnu Rusyd and MA Al-Jawami Bandung Regency. The analysis used multiple linear regression analysis is used to determine how much influence X1 and X2 have on Y either simultaneously or partially. The results of this study show that the Principal’s Leadership and Teacher Competence have a significant positive effect on Student Learning Achievement simultaneously or partially.